Development of Authentic Assessment Instruments Through High-Level Botanical Practicums to Improve Science Process Skills - Elfrida Elfrida; Nursamsu Nursamsu; Fauziyah Harahap (Jurnal Penelitian Pendidikan IPA, 2022)
The Auntentik Assessment Instrument is part of the achievement indicator in obtaining information to measure aspects of student knowledge in the learning process. The measurement process carried out for students in the assessment instrument both individually and in groups consists of three affective, psychomotor and cognitive aspects. Ethnobiological studies are part of the understanding of people's culture regarding the knowledge of plants. Science process skills activities are the implementation of an action carried out by students in practicum learning. The basis of the research objectives is to develop an assessment instrument on a high-level botanical practicum learning tool in measuring students' science process skills and measuring feasibility tests and limited tests of assessment instruments in the implementation of science process skills practicum learning activities. The implementation of the method in the research is a development method. The results of this study consist of three aspects of assessment from expert validation, namely aspects of content validity, presentation aspects and language aspects are declared feasible. Meanwhile, the student's response to the assessment instrument was stated to be good to use as a measuring tool in the assessment of students to carry out a high-level botanical practicum.